Argon plasma coagulation for Barrett’s esophagus with low-grade dysplasia: a randomized trial with long-term follow-up on the impact of power setting and proton pump inhibitor dose - Wronska, Ewa; Polkowski, Marcin; Orlowska, Janina; Mroz, Andrzej; Wieszczy, Paulina; Regula, Jaroslaw (Endoscopy, 2020)
Background This study evaluated the impact of power setting and proton pump inhibitor (PPI) dose on efficacy and safety of argon plasma coagulation (APC) of Barrett’s esophagus (BE) with low-grade dysplasia (LGD).Methods 71 patients were randomized to APC with power set at 90 W or 60 W followed by 120 mg or 40 mg omeprazole. The primary outcome was the rate of complete (endoscopic and histologic) ablation of BE at 6 weeks. Secondary outcomes included safety and long-term efficacy.Results Complete ablation rate in the 90 W/120 mg, 90 W/40 mg, and 60 W/120 mg groups was 78 % (18/23; 95 % confidence interval [CI] 61–95), 60 % (15/25; 95 %CI 41–79), 74 % (17/23; 95 %CI 56–92), respectively, at 6 weeks and 70 % (16/23; 95 %CI 51–88), 52 % (13/25; 95 %CI 32–72), and 65 % (15/23; 95 %CI 46–85) at 2 years post-treatment (differences not significant). Additional APC was required in 28 patients (23 residual and 5 recurrent BE). At median follow-up of 108 months, 66/71 patients (93 %; 95 %CI 87–99) maintained complete ablation. No high-grade dysplasia or adenocarcinoma developed. Overall, adverse events (97 % mild) did not differ significantly between groups. Chest pain/discomfort was more frequent in patients receiving 90 W vs. 60 W power (P < 0.001). One patient had esophageal perforation and two developed stenosis.Conclusions APC power setting and PPI dose did not impact efficacy and safety of BE ablation. Complete ablation of BE with LGD was durable in > 90 % of patients, without any evidence of neoplasia progression in the long term.